Development of Home Appliances Controller with DTMF Signal - Nawir, N.A.A.; Isira, A.S.M.; Yunus, N.A.M.; Basari, A.A. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
This paper presents the development of home appliances controller design that utilizes Dual-Tone Multi Frequency (DTMF) signal from the landline telephone. The device contains microcontroller that links with a decoder IC that converts DTMF signal into binary codes and vice versa. It is proven that the device enables residents to send and receive signal from outside the house; thus enabling them to control the appliances at home. Finally, the results from an experimental setup found that the device is proven to be working.